PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA PERAWAT RUMAH SAKIT JIWA TAMPAN PROVINSI RIAU) - Sitorus, Michael Jadi Habonaran; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of Transformational Leadership Style and Organizational Climate on Employee Performance in Nurses in the Handsome Mental Hospital of Riau Province. Where two independent variables and one bound are proposed, namely the Transformational Leadership Style and Organizational Climate as independent variables and Employee Performance acts as the dependent variable.This research method is descriptive and using the SPSS 21 program, where the sample used is Nurse Handsome Mental Hospital of Riau Province with respondents as many as 56 people. For sampling techniques using the census method. Data collection techniques through questionnaires and interviews. The results of the analysis use validation tests. Determination test, simple linear regression test, multiple linear regression test, t test, and f test so that it can be understood that the Transformational Leadership Style has a significant effect on Employee Performance in nurses in Riau Province Handsome Mental Hospital, Organizational Climate has a significant effect on Employee Performance at Home Nurses Handsome Mental Disease of Riau Province, and Transformational Leadership Style and Organizational Climate have a significant effect on Employee Performance in Nurses, Handsome Mental Hospital, Riau Province. Keywords: Transformational Leadership Style, Organizational Climate and Employee Performance